(3OjhGf GHf gGfF GdGfOdSis - (3GHf gGfjA GdCfOdSj , eMeO Hf gGfjA Hf eMeO Hf SYOhf GdCROj GdCfOdSj, CHh GdbGSe,J (B362 (3g` s
(3ChdgG (B:s
(3CUGNJ abGdJ hbY CLQOTjWe hTGeJ hbGdJ HQb CHjV eNOe s
(3BNQgG (B:s
(3Lejd QbGO ai cag hSW hfMf ebOhfS ajg hWQahf s
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde ajg VHWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B130 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B88s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(5646) s
Keywords: (3GdCOHs